2017
DOI: 10.1061/(asce)gt.1943-5606.0001781
|View full text |Cite
|
Sign up to set email alerts
|

Shearing Behavior of Tire-Derived Aggregate with Large Particle Size. II: Cyclic Simple Shear

Abstract: Although Tire-Derived Aggregate (TDA) has been used widely as lightweight fill in civil engineering applications, the properties governing its response under cyclic loading are not well understood. Reliable data on the evolution of shear modulus and damping ratio with cyclic shear strain amplitude are needed for the prediction of the seismic response of TDA fills, especially those with larger particle sizes up to 300 mm (Type B TDA). This study presents the results of cyclic simple shear tests performed on Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…This paper presents the results of TDA internal direct shear and TDA-concrete interface direct shear tests, which are the first to fully characterize the shear stress-displacement relationships and failure envelopes for Type B TDA. A companion paper (McCartney et al 2017) presents corresponding cyclic simple shear data obtained using the same device in an alternate configuration.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the results of TDA internal direct shear and TDA-concrete interface direct shear tests, which are the first to fully characterize the shear stress-displacement relationships and failure envelopes for Type B TDA. A companion paper (McCartney et al 2017) presents corresponding cyclic simple shear data obtained using the same device in an alternate configuration.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in volumetric contraction is observed with increasing normal stress, although the volumetric strains are not as significant as those observed in the direct shear tests on TDA reported by Ghaoowd et al (2017). In the direct shear tests reported by Ghaaowd et al (2017), the TDA was observed to initially contract to a volumetric strain of up to 303 0.8% at a horizontal displacement, after which dilation was observed. A dilation angle of 1.2 to 304 3.7° was observed for the TDA.…”
Section: Pullout Tests On Gga 275mentioning
confidence: 93%
“…The low unit weight, high thermal insulation capacity, and high permeability of TDA are distinctive properties that provide several advantages for using TDA in civil engineering applications (Humphrey 2005(Humphrey , 2008. Further, Ghaaowd et al (2017) and McCartney et al (2017) found that TDA has similar shear strength properties to granular soils and also has high damping ratio. TDA has been used widely in different civil engineering applications including subgrade replacement and backfills for embankments, retaining walls and trenches (Ahmed and Lovell 1993;Bosscher et al 1993;Bosscher et al 1997;Tweedie et al 1998;Yoon et al 2006;Humphrey 2008;Geisler et al 1989;Lee et al 1999;Tandon et al 2009;Meles et al 2013;Ahn and Cheng 2014;CalRecycle 2015;Mahgoub and El Naggar 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Scrap rubber tires also have unique engineering properties in addition to their low thermal conductivity, including their light-weight, high frictional resistance and high damping (Zornberg et al 2004;Ghaaowd et al 2017;McCartney et al 2017;Noorzad and Raveshi 2017). Scrap rubber tires have been widely used as a replacement aggregate in many geotechnical applications, such as retaining walls, pavements, and embankments (Humphrey and Eaton 1995;Bosscher et al 1997;Youwai and Bergado 2003).…”
Section: Introductionmentioning
confidence: 99%